Nutritional Information Provision to Cancer Patients and Their Relatives Can Promote Dietary Behavior Changes Independent of Nutritional Information Needs. (3rd April 2018) - van Veen, Merel R.; Winkels, Renate M.; Janssen, Silvie H. M.; Kampman, Ellen; Beijer, Sandra
ABSTRACT: We investigated whether obtaining nutritional information influences reported changes in dietary behavior in cancer survivors and their relatives and whether nutritional information needs influence this association. We included 239 cancer survivors and their relatives, recruited from an online panel of cancer survivors and relatives. This panel completed a survey about their experiences with nutritional information provision by healthcare professionals and the media in the period after diagnosis, their information needs regarding nutrition and cancer, and whether they changed their dietary behavior since diagnosis. The survey showed that 56% of respondents obtained nutritional information, mostly during treatment. Respondents who obtained nutritional information more often reported to have altered their dietary behavior after diagnosis. This association was not altered by having information needs. The reported changes in dietary behavior were coherent with the recommendations of the World Cancer Research Fund: respondents reported to choose less products that promote weight gain, increased intake of plant foods, and decreased meat and alcohol use. Respondents who obtained nutritional information more often changed their dietary behavior, regardless whether they had nutritional information needs. This might be an indication that healthcare professionals should provide nutritional information not only to those expressing a need for nutritional information.